Trust and IPO underpricing - Li, Xiaorong; Wang, Steven Shuye; Wang, Xue (Journal of Corporate Finance, 2019)
This study examines the impact of trust on initial public offering (IPO) underpricing using a large sample of IPO firms in China. We find that firms in regions of high social trust have lower underpricing, consistent with the notion that IPO firms in low-trust regions have to offer greater underpricing to secure participation. This result is robust to a battery of sensitivity tests and after controlling for endogeneity using instrumental variables. We also find that the negative relation between social trust and underpricing is more prominent for small and growth firms, and firms in high-tech industries, consistent with trust playing a more important role in asymmetric information environments. This relation is less pronounced for firms with high insider ownership and political connections, suggesting that investors rely less on trust in these cases; it is less salient when firms are in regions with high quality legal institutions and high average education levels, consistent with trust being a substitute for formal institutions.